Efektivitas return on asset terhadap return saham pada perusahaan: studi manajemen keuangan - Irdawati; Ng, Suwandi; Safira, Riata Dheasita; Prananingrum, Dwi Kartika; Azizi, Muhammad (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2023)
The purpose of this paper is to analyze the Effectiveness of Return On Assets Against Stock Returns in Companies through analysis of literature studies in the field of financial management. The method used in this research is literature research by reviewing some of the results of previous studies. This scientific article was written using qualitative methods and literature research with the help of the latest references obtained from Google Schoolers and Mendeley citation searches. Based on the review conducted, it means that Return On Assets has a positive and significant influence on Stock Returns. So that ROA has a significant effect on stock prices, where the profit generated by the company increases, the results obtained by the company also increase in terms of the level of profitability generated.